Streamlining Venepuncture: Reducing Time Wasted and Improving Patient Care on a Specialist Eating Disorder Unit (SEDU) - Leah Jacob; John Adam; Robert Hyder-Wilson; Ewa Zadeh (BJPsych Open)
Aims: Specialist eating disorder units (SEDUs) are unique among psychiatric units, in that there is a high incidence of electrolyte derangements due to the pathophysiology of refeeding. This requires careful monitoring of blood parameters with frequent venepuncture which often can be difficult due to strict mealtimes and post meal supervision as well as required group attendance in the SEDU.